Ecogenomics of virophages and their giant virus hosts assessed through time series metagenomics. Issue 1 (December 2017) - Roux, Simon; Chan, Leong-Keat; Egan, Rob; Malmstrom, Rex; McMahon, Katherine; Sullivan, Matthew
Abstract Virophages are small viruses that co-infect eukaryotic cells alongside giant viruses (Mimiviridae ) and hijack their machinery to replicate. While two types of virophages have been isolated, their genomic diversity and ecology remain largely unknown. Here we use time series metagenomics to identify and study the dynamics of 25 uncultivated virophage populations, 17 of which represented by complete or near-complete genomes, in two North American freshwater lakes. Taxonomic analysis suggests that these freshwater virophages represent at least three new candidate genera. Ecologically, virophage populations are repeatedly detected over years and evolutionary stable, yet their distinct abundance profiles and gene content suggest that virophage genera occupy different ecological niches. Co-occurrence analyses reveal 11 virophages strongly associated with uncultivatedMimiviridae, and three associated with eukaryotes among theDinophyceae, Rhizaria, Alveolata, andCryptophyceae groups. Together, these findings significantly augment virophage databases, help refine virophage taxonomy, and establish baseline ecological hypotheses and tools to study virophages in nature. Virophages are recently-identified small viruses that infect larger viruses, yet their diversity and ecological roles are poorly understood. Here, Roux and colleagues present time series metagenomics data revealing new virophage genera and their putative ecological interactions in two freshwater lakes.